Highly Scalable, Closed‐Loop Synthesis of Drug‐Loaded, Layer‐by‐Layer Nanoparticles. (3rd January 2016) - Correa, Santiago; Choi, Ki Young; Dreaden, Erik C.; Renggli, Kasper; Shi, Aria; Gu, Li; Shopsowitz, Kevin E.; Quadir, Mohiuddin A.; Ben‐Akiva, Elana; Hammond, Paula T.
Abstract : Layer‐by‐layer (LbL) self‐assembly is a versatile technique from which multicomponent and stimuli‐responsive nanoscale drug‐carriers can be constructed. Despite the benefits of LbL assembly, the conventional synthetic approach for fabricating LbL nanoparticles requires numerous purification steps that limit scale, yield, efficiency, and potential for clinical translation. In this report, a generalizable method for increasing throughput with LbL assembly is described by using highly scalable, closed‐loop diafiltration to manage intermediate purification steps. This method facilitates highly controlled fabrication of diverse nanoscale LbL formulations smaller than 150 nm composed from solid‐polymer, mesoporous silica, and liposomal vesicles. The technique allows for the deposition of a broad range of polyelectrolytes that included native polysaccharides, linear polypeptides, and synthetic polymers. The cytotoxicity, shelf life, and long‐term storage of LbL nanoparticles produced using this approach are explored. It is found that LbL coated systems can be reliably and rapidly produced: specifically, LbL‐modified liposomes could be lyophilized, stored at room temperature, and reconstituted without compromising drug encapsulation or particle stability, thereby facilitating large scale applications. Overall, this report describes an accessible approach that significantly improves the throughput of nanoscale LbL drug‐carriers that show low toxicity and are amenable to clinically relevant storage conditions. Abstract : The highly scalable preparation of drug‐loadable, layer‐by‐layer nanoparticles is described for a variety of formulations below 150 nm in size. This work demonstrates a method to generate layer‐by‐layer drug‐carriers in a manner that is both facile and gives much higher throughput than traditional methods. Results also reveal that the generated nanoparticles possess clinically relevant shelf lives as well as compatibility with long‐term freeze‐dried storage.